2006
DOI: 10.1016/j.vetpar.2006.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Severe weight loss in lambs infected with Giardia duodenalis assemblage B

Abstract: An outbreak of giardiasis was observed in a sheep farm in Central Italy. Infected lambs (30-90 days of age) showed a malabsorption syndrome, decreased weight gain and impairment in feed efficiency. The most relevant clinical sign was the excretion of malodorous and poorly formed faeces, whereas diarrhoea was rarely observed in the flock. Laboratory investigations revealed the presence of Giardia in affected animals, while no other significant viral, bacterial or parasitic pathogens were identified in faeces or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 24 publications
(32 reference statements)
1
70
0
3
Order By: Relevance
“…Giardia is widely distributed in sheep with prevalence's of 1.5% to 55.6% reported (Feng and Xiao, 2011). The host specific assemblage E (livestock genotype) and the zoonotic assemblage A have been predominately reported in sheep (Giangaspero et al, 2005;Ryan et al, 2005;Santín et al, 2007;Geurden et al, 2008, Gómez-Muñoz et al, 2009Sprong et al, 2009;Yang et al, 2009;Lebbad et al, 2010;Nolan et al, 2010;Robertson et al, 2010;Sweeny et al, 2011;Feng and Xiao, 2011;Gómez-Muñoz et al, 2012;Zhang et al, 2012), although assemblage B has also been reported (Aloisio et al, 2006;Zhang et al, 2012). Previous studies conducted in Australia have examined lambs in Western Australia (WA) and Victoria (Vic) only (Ryan et al, 2005;Yang et al, 2009;Nolan et al, 2010;Sweeny et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Giardia is widely distributed in sheep with prevalence's of 1.5% to 55.6% reported (Feng and Xiao, 2011). The host specific assemblage E (livestock genotype) and the zoonotic assemblage A have been predominately reported in sheep (Giangaspero et al, 2005;Ryan et al, 2005;Santín et al, 2007;Geurden et al, 2008, Gómez-Muñoz et al, 2009Sprong et al, 2009;Yang et al, 2009;Lebbad et al, 2010;Nolan et al, 2010;Robertson et al, 2010;Sweeny et al, 2011;Feng and Xiao, 2011;Gómez-Muñoz et al, 2012;Zhang et al, 2012), although assemblage B has also been reported (Aloisio et al, 2006;Zhang et al, 2012). Previous studies conducted in Australia have examined lambs in Western Australia (WA) and Victoria (Vic) only (Ryan et al, 2005;Yang et al, 2009;Nolan et al, 2010;Sweeny et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Three genotypes of G. duodenalis have been identified in sheep, genotype E, and the two zoonotic genotypes, genotype A and B (Giangaspero et al, 2005, Ryan et al, 2005, Aloisio et al, 2006, van der Giessen et al, 2006Castro-Hermida et al, 2007;Santin et al, 2007;Geurden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Giardiosis in cattle is associated with a high morbidity, significant production loss and potential transmission to other hosts [1,4,18]. Prevalence rates may vary according to the age of the animals, design of the study, diagnostic techniques, geographical location, climatological conditions and management practices [4,18].…”
Section: Discussionmentioning
confidence: 99%